Establish of important habitats for dryland mountain biodiversity by their lichen species: (In case of Baraat mountain, Khujirt village, Mӧst sum, Khovd aimag) - Ochirbat, Enkhtuya; Samiya, Javkhlan; Tungalag, Munkhzul; Purevdorj, Byambasuren (Mongolian Journal of Botany, 2022)
The study of lichens, which are species sensitive to environmental changes, is of great use. As a result of our analysis of lichen biodiversity, it is shown that the habitats of dry grass meadows from the Baraat ridge of the village Hujirt-Bagh from the somon Must, Khuvd Aimak are extremely rare in the Altai-Sayan region and are important habitats for the gene pool and habitat of the rare genetic resources of lichens. As a result of the research, 52 species from 32 genera of 17 families were registered, of which 7 species were found for the first time in the mountainous dry steppe vegetation of the geographical region of Mongolia Altai. And also found extremely rare and Altai-Sayan endemics Evernia terrestris and another 12 species with the status of rarity. According to available data, this mountainous area can be considered the southernmost boundary of the lichen range, for which a question of protection should be raised. The study also determined that the diversity of substrate habitats is more important than the size of the area of the species range, taking into account, all known lichen species as referring to the environment and the availability of moisture on the surface of the growth, and how they adapt. In the modern era of climate change, local protection of this unique ecosystem of habitats isolated in dry and arid mountainous areas will help the Bodonchu River, which is important for the diversity of extremely rare and rare vascular and nonvascular (cryptogam) plant species also small mammals of reptiles and birds. The protection of the habitat of one of the main sources of the Bodonça River Basin and the livelihoods of pastoralists must be valued. Хуурай гандуу уулархаг нутгийн биологийн олон янз байдалд чухал амьдрах орчинг хагийн төрөл зүйлээр тогтоох нь (Ховд аймгийн Мөст сум, Хужирт багийн Бараат уулын жишээн дээр) Хураангуй: Орчны өөрчлөлтийн мэдрэг төрөл зүйл болох хагийн судалгаагаар Ховд аймгийн Мөст сум, Хужирт багийн Бараат уулын алаг өвст бушилзат нугажуу хээрийн амьдрах орчинг Алтай-Соёны бүс нутгийн хувьд нэн ховор, ховор хагийн генетик нөөцийн удмын сан, амьдрах орчны хувьд чухал газар нутаг болохыг нотлов. Судалгааны үр дүнд 17 овгийн 32 төрлийн 52 зүйл бүртгэснээс Монгол-Алтайн уулын хээрийн тойрогт шинээр 7 зүйл, Алтай-Соёны эндемик бөгөөд нэн ховор Evernia terrestris, мөн ховор статустай 12 зүйл хагийн тархацын хамгийн өмнөд хязгаартаа орших уулархаг бүс нутаг гэж үзэн Ховд аймгийн орон нутгийн хамгаалалтад авах асуудлыг хөндөж байна. Мөн судалгаагаар мэдэгдэж буй нийт зүйл хагийг хүрээлэн буй орчны болон ургах гадаргуун хур чийгийн хүртээмжтэй хэрхэн холбогдож, хэрхэн дасан зохицож буй шинжийг тус тус харгалзан зүйлийн тархцад талбайн их багаас илүүтэй амьдрах орчны субстратын олон янз байдал чухал гэдгийг тогтоов. Уур амьсгалын өөрчлөлтийн өнөө цаг үед хуурай гандуу уулархаг нутагт тусгаарлагдсан энэхүү өвөрмөц амьдрах орчны экосистемийг орон нутгийн хамгаалалтад авснаар нэн ховор, ховор цэцэгт гуурст болон спорт гуурсгүй (криптогам) ургамлын төрөл зүйлийн олон янз байдал, жижиг хөхтөн, хэвлээр явагчид болон шувуудад ач холбогдол бүхий Бодонч голын ай савын нэг томоохон эх ундрагын амьдрах орчныг хамгаалах, малчдын амьжиргааг тэтгэх зэрэгт үнэлж баршгүй ач холбогдол өгөх учиртай. Түлхүүр үгс: Бараат уул, нэн ховор, ховор хаг, үйл ажиллагааны мэдрэг шинж